MENEMUKAN KEBERMAKNAAN HIDUP MELALUI KONSELING KELOMPOK BERBASIS NILAI-NILAI FILOSOFIS MASYARAKAT JAWA - taufik, ismail (AflahConsilia : Jurnal Bimbingan dan Konseling, 2024)
This article describes group counseling based on indigenous or local wisdom to find the meaning of life by instilling the philosophical valuesof javanesse society. Several teachings containing the philosophical valuesof javanesse society are often expressed in javanese terms. The type of research used in thus research is libarry research, where data is collected by conducting a review study of books, literature, notes, and reports has something to do with the problem being solved. The resulth of this research are that group counseling based on philosophical valuesof javanesse society is relevant and can be internalized in counseling sessions to help clients find meaning in life., for example Suro Diro Jayanigrat Lebur Dening Pangastuti, Alon-Alon Waton Kelakon, Aja Gumunan, Aja Getunan, Aja Kagetan, Aja Aleman, Ngunduh Wohing Pakarti, dan Nrimo ing Pandum, Makaryo ing Nyoto. The meaning of philosophical valuesof javanesse society has a deep meaning and can be used to help clients find the meaning of life. Simply put, humans must admit that they have and opposite side and can accept whatever happens or we must surrender to everythings that comes to us after trying as hard as possible in life. The steps or stages of group counseling based on philosophical valuesof javanesse society are the opening stage, presenting the problem, exploring the background of the problem, solving the problem, and the last is closing.